Das Paraibatal: Wandlungen einer brasilianischen Landschaft - Neufeldt, Lieselotte (ERDKUNDE, 1953)
During the 19t h century the Paraiba valley experienced very great development as a result of the first large scale coffee plantings in Brazil. From 1860 onwards, however, yields deteriorated from lack of manuring, and soon the valley reverted to extensive livestock farming. Today it is again experiencing a revival, this time based on the cultivation of rice, fruit and vegetables, in addition to afforestation and to dairy farming.